Imagination et construction mentale La fabrique du discours scientifique - Orellana-González, Eliza; Spinelli Sanchez, Océane; Balbin-Estanguet, Tom; Sergues, Victor; TAFFIN, Ninon (Schol@, 2022)
Imagination and mental construction are processes attached to the development of scientific discourse and research in archaeological sciences. Past human groups built symbolic thoughts, shaped and exploited their environments, and these concepts enabled them to design new objects from raw materials. This book uses diachronic and interdisciplinary case studies to examine how imagination and mental construction interact to produce ideas or material objects in past societies and in current research. It also examines the elaboration of scientific discourse, a process that is based on the researcher's own mental constructs and that is enriched today by a critical approach to past discourses as well as by the contribution of new methods and methodologies.